Is Experience Value Still Relevant? Evidence from Tidung Island’s Digital Tourism - Eko Yuliawan; Altatit Dianawati; Sentot Eko Baskoro; Aldi Friatna Dira; TB Firman Wiraatmadja (Lentera Ilmu Nusantara, 2026)
This study is motivated by the growing role of digital technology in shaping tourist behavior, particularly its influence on revisit intention in marine tourism destinations. Previous studies have generally examined digital service quality, social media engagement, and revisit intention separately, while limited research has integrated these variables simultaneously in the context of Indonesian marine tourism destinations, creating a research gap regarding the mediating role of perceived experience value. Therefore, this study aims to analyze the effect of digital service quality and social media engagement on tourist revisit intention, with perceived experience value as a mediating variable. This study adopts a quantitative approach using an explanatory research design. Data were collected through questionnaires distributed to 170 respondents who had visited Tidung Island within the past year using purposive sampling, and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that digital service quality and social media engagement have a positive and significant effect on tourist revisit intention. Furthermore, digital service quality significantly affects perceived experience value, whereas social media engagement does not, and perceived experience value does not significantly affect revisit intention. These findings indicate that digital factors have a stronger direct influence on revisit intention than indirect effects through experiential evaluation. This study contributes theoretically by enriching the literature on digital tourism behavior and, practically, by providing insights for tourism managers to strengthen digital services and social media strategies to improve tourist loyalty and revisit intention.